2011
DOI: 10.3324/haematol.2011.049627
|View full text |Cite
|
Sign up to set email alerts
|

Clinically defined chemotherapy-associated bowel syndrome predicts severe complications and death in cancer patients

Abstract: BackgroundNeutropenic patients are at risk of abdominal complications and yet the incidence and impact of these complications on patients' morbidity and mortality have not been sufficiently evaluated. We aimed to assess a clinical rule for early detection of abdominal complications leading to death or transfer to intensive care in patients with chemotherapy-associated neutropenia. Design and MethodsThis observational multicenter study was carried out in seven German hematology-oncology departments. For inclusi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
15
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 31 publications
0
15
1
Order By: Relevance
“…The 14.2% incidence of CDI in this study compares to 5–33% rates reported among various neutropenic cancer patients including SCT recipients , albeit ours reported the cumulative incidence of CDI following several cycles of antineoplastic therapy including high‐dose myeloablative regimens delivered over approximately 1 year, as compared to shorter follow‐up periods in other reports .…”
Section: Discussioncontrasting
confidence: 78%
“…The 14.2% incidence of CDI in this study compares to 5–33% rates reported among various neutropenic cancer patients including SCT recipients , albeit ours reported the cumulative incidence of CDI following several cycles of antineoplastic therapy including high‐dose myeloablative regimens delivered over approximately 1 year, as compared to shorter follow‐up periods in other reports .…”
Section: Discussioncontrasting
confidence: 78%
“…1 Neutropenic colitis as its most severe complication has been associated with increased mortality. 2 Recent evidence suggests an even more complex role for chemotherapy-induced mucositis. Two independent groups were able to demonstrate in their respective mouse models that disruption of the mucous membranes' barrier function may enable a hitherto unknown mode of action of cytotoxic treatment.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have demonstrated that the bioavailability of posaconazole is significantly enhanced when given with food, particularly a high-fat meal (5,9), presumably because of an increase in dissolution. Patients at risk for IFD are often critically ill and may be unable to eat because of mucositis, severe nausea, neutropenic enterocolitis, or graft-versus-host disease (12,14,18). In these patients, absorption of posaconazole may be enhanced by dividing posaconazole doses or by administering the drug with a liquid nutritional supplement or acidic beverage (8,9).…”
mentioning
confidence: 99%